Hambatan Determinan Penerapan Code Blue pada Rumah Sakit di Aceh - Sahputri, Anita; Zulhilmi, Zulhilmi (Jurnal Ragam Pengabdian, 2026)
The code blue system aims to provide a rapid response to cardiac or respiratory arrest events. Implementation of this system is crucial to increase the chances of patient safety. However, in various hospitals, including in Aceh, the implementation of code blue faces several obstacles that can reduce its effectiveness. The purpose of this study is to analyze the obstacles to the implementation of code blue in hospitals in Aceh. The research design is an analytical correlation and a time-based design approach, namely cross-sectional. This study will be conducted from March to September 2025. The population in this study are nurses in hospitals with a sample of 50 people. The measurement tool used is a questionnaire about the obstacles to code blue and the implementation of code bule. The analysis will use univariate and bivariate analysis with the chi-square test. The results of the study indicate that there is a relationship between facilities and infrastructure factors (p = 0.009), contribution and communication (p = 0.001), regularity of training and simulation (p = 0.000), and managerial aspects in code implementation (p = 0.000) with the implementation of code blue in hospitals in Aceh. It is concluded that each factor plays an important role in implementing good code blue implementation in hospitals.